Role of IFPRI in agricultural research and rural development in India - Joshi, P K; Kumar, Anjani (Indian Farming, 2018)
The complexity to achieve food and nutritional security is not limited to the existing challenges but equally dependent on changing variables from policy implementation, climate change to changing consumer behaviours. The IFPRI has done remarkable works and contributed significantly to promote agricultural research and rural development in India. It will continue to do pioneering work to evolve policy solutions to eradicate hunger and poverty from India. The approach of IFPRI’s work is based on solid partnership with NARS and other development departments. The IFPRI will continue to foster collaboration and partnership to accomplish the shared objectives of ensuring sustainable and inclusive growth in India.